2010
DOI: 10.1099/ijs.0.011783-0
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium pyruviciproducens sp. nov., a pyruvic acid producer

Abstract: A coryneform strain, 06-1773O T (5WAL 19168 T ), derived from a groin abscess sample was characterized using phenotypic and molecular taxonomic methods. Comparative analyses revealed more than 3 % divergence of the 16S rRNA gene sequence and about 10 % divergence of the partial rpoB gene sequence from the type strain of Corynebacterium glucuronolyticum. The strain could also be differentiated from C. glucuronolyticum by a set of phenotypic properties. A DNA-DNA relatedness study between strain WAL 19168 T and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…For example, within the Corynebacterium genus, 18 novel species were validly described from 2004 to 2009. A total of 5 of these, namely, Corynebacterium freiburgense (12), Corynebacterium pyruviciproducens (26), C. mastitidis (10,18), C. massiliense (18), and C. ureicelerivorans (11,31), were also identified in our study. When we calculated phylogenetic trees based on partial 16S rRNA sequences (Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…For example, within the Corynebacterium genus, 18 novel species were validly described from 2004 to 2009. A total of 5 of these, namely, Corynebacterium freiburgense (12), Corynebacterium pyruviciproducens (26), C. mastitidis (10,18), C. massiliense (18), and C. ureicelerivorans (11,31), were also identified in our study. When we calculated phylogenetic trees based on partial 16S rRNA sequences (Fig.…”
mentioning
confidence: 96%
“…Of those, 60 isolates (0.4‰; see Table S1 in the supplemental material) had a 16S rRNA gene homology of Ͻ99% to members of accepted taxa on the date of the first interpretation. A total of 11 of the 60 sequences with a 16S rRNA homology of Ͻ99% in the first-time analysis could be allocated to a species established during the study term as a novel species by others: Acinetobacter septicus (16,20), Brevibacterium ravenspurgense (17), Corynebacterium freiburgense (12), Corynebacterium massiliense (n ϭ 2) (18), C. mastitidis (10,18), C. pyruviciproducens (26), C. ureicelerivorans (11,31), Neisseria zoodegmatis (28), Paenibacillus barengoltzii (21), and the reclassified Campy- lobacter ureolyticus (previously known as Bacteroides ureolyticus) (27). We calculated dendrograms to assess phylogenetic relationships (Fig.…”
mentioning
confidence: 99%
“…T (1). These observations as well as heterogeneities in the 16S rRNA sequences are presented in this report.…”
mentioning
confidence: 62%
“…These observations as well as heterogeneities in the 16S rRNA sequences are presented in this report. In the species description publication, Tong and colleagues (1) reported that the C. pyruviciproducens type strain was highly sensitive to ampicillin, ceftriaxone, clindamycin, and erythromycin. Since no other information concerning the antimicrobial susceptibility of C. pyruviciproducens has been published to date, we present in this report detailed data on the antimicrobial susceptibility testing of isolates from our laboratories, including new susceptibility data for the strain 06-17730 T using an extended panel of antimicrobials.…”
mentioning
confidence: 99%
See 1 more Smart Citation